Nonlinear association of serum uric acid and C-peptide with arterial stiffness in patients with type 2 diabetes: a real-world study - He, Youming; Jin, Yufeng; Gao, Mengqi; Jin, Jing; Chen, Ke; Zhou, Lixin; Shi, Jingbin; Luo, Bei; Liang, Yongqian (Frontiers in Endocrinology, 2026)
BackgroundDiabetes has become one of the most serious and prevalent chronic diseases, and its cardiovascular complications are responsible for over 50% of diabetes-related deaths. However, the relationships between uric acid (UA) and C-peptide on arterial stiffness (AS) in patients with type 2 diabetes mellitus (T2DM) are still poorly understood. This study aimed to evaluate the associations between UA and C-peptide with AS in T2DM patients.MethodsIn this cross-sectional study of 1,715 participants with T2DM, we recorded levels of fasting UA, C-peptide, and other characteristics. Elevated AS was defined as a brachial-ankle pulse wave velocity (baPWV) of ≥1,400 cm/s. Logistic regression and a restricted cubic spline (RCS) model were employed to assess the associations of UA and C-peptide with AS.ResultsFasting UA and C-peptide levels were independently and significantly associated with elevated AS in patients with T2DM, as determined by multivariate analyses (P < 0.05). Notably, RCS analyses revealed nonlinear relationships with threshold effects between fasting UA, C-peptide, and elevated AS (P for nonlinearity < 0.05). Compared to patients with C-peptide levels < 0.580 μg/L, those with levels ≥ 0.580 μg/L had an approximately 87% relatively higher odds of elevated AS (OR = 1.87, 95% CI: 1.32, 2.65).ConclusionThe elevated AS odds in patients with T2DM were nonlinearly associated with the levels of serum fasting UA and C-peptide.